If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + (x + -9) = 4(x + -10) Reorder the terms: 4x + (-9 + x) = 4(x + -10) Remove parenthesis around (-9 + x) 4x + -9 + x = 4(x + -10) Reorder the terms: -9 + 4x + x = 4(x + -10) Combine like terms: 4x + x = 5x -9 + 5x = 4(x + -10) Reorder the terms: -9 + 5x = 4(-10 + x) -9 + 5x = (-10 * 4 + x * 4) -9 + 5x = (-40 + 4x) Solving -9 + 5x = -40 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + 5x + -4x = -40 + 4x + -4x Combine like terms: 5x + -4x = 1x -9 + 1x = -40 + 4x + -4x Combine like terms: 4x + -4x = 0 -9 + 1x = -40 + 0 -9 + 1x = -40 Add '9' to each side of the equation. -9 + 9 + 1x = -40 + 9 Combine like terms: -9 + 9 = 0 0 + 1x = -40 + 9 1x = -40 + 9 Combine like terms: -40 + 9 = -31 1x = -31 Divide each side by '1'. x = -31 Simplifying x = -31
| 6(3n-5)=(9n+8)+5 | | ax+2=aw | | 4=t-5s | | 5n-8=-48 | | (x^3+4x^2)-(2x-8)=0 | | 3n-9=-27 | | 3-6(4+8n)=-21+10n | | 20r^2-41r+20=0 | | x(10x+24)=0 | | (s+16)(s+81)=0 | | 7-3x=15+5x | | 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 |